Misrepresentation of Chinese culture in American picture books through written and visual languages - Wangbei, Tu (Vestnik za tuje jezike, 2025)
Language is a communication system which consists of signs, symbols, gestures, and so on. In picture books, a special genre of children’s books, pictures can be regarded as a visual language because meaning can be conveyed from the authors to readers by pictures. However, there are a number of limitations with regard to the cultural connotations implied in the picture-word language system in picture books, and previous studies found there were ste-reotypes of Chinese culture and Chinese people in American picture books. Using a mixed methodology approach, the author selected 78 picture books created by American authors, including Chinese Americans, from an initial sample of 3,000, and subjected them to dis-course analysis to examine the misrepresentations of Chinese culture. The results showed three main types of misrepresentation of Chinese culture in picture books and explored the reasons for this. The misrepresentations included: (1) the full view of Chinese culture is overshadowed by the excessive attention and localization of cultural symbols, such as the Chinese dragon and the Spring Festival; (2) the confusion of Asian cultures in visual language and written language weakens the uniqueness of Chinese culture; and (3) information disorder weakens the authenticity of Chinese culture. The reasons for these misrepresenta-tions are rooted in the attitudes towards multiculturalism in American, including in relation to Chinese Americans. The misinterpretations result in the following issues: (1) Chinese culture is equated with the culture of Chinese Americans; (2) Chinese culture is regarded as static, which leads to serious homogenization; (3) the sightseeing attitude towards Chinese culture results in an excessive focus on cultural symbols. Therefore, the misrepresentations and even stereotypes of Chinese and Chinese culture have been solidified by these books.
Keywords: American picture books; ameriške slikanice; Chinese culture; kitajska kultura; misrepresentation; multimodal; multimodalnost; napačno prikazovanje; visual language; vizualni jezik